SOLVOTHERMAL SYNTHESIS OF Ti02 NANOMATERIALS FOR THE REMEDATION OF ORANGE II DYE - ,, MUHAMMAD ZULFIQAR (2016)
Many kinds of dyes are being used in industrial operation especially in textile sectors and released in open atmosphere in the form of wastewater. The main objective of this study is to synthesize the different Ti02 nanostructures (TNSs) via a solvothermal synthetic route with the assistant of sodium hydroxide (NaOH) solution. TNSs length ranging up to 1600 nm and diameter 2 to 120 nm were prepared and confirmed through the microscopic image analysis. The effects of solvents including water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol and N, NDimethylformamide (DMF) on forms and morphologies of TNSs were investigated. The microstructures and morphologies of single-walled, multi-walled and sheet-like TNSs were confirmed through characterizations. Evolution of different size of TNSs is accompanied by significant variations of band gap from 2.81 to 3.15 eV, and surface areas from 25.42 to 260.58 m2/g.